Verbal and Visual Elements Found in Barenbliss Advertisement - Ni Wayan Kasni; Ni Luh Sriyanti; Dewa Ayu Dyah Pertiwi Putri (Humanitatis : Journal of Language and Literature, 2026)
The aims of this research were to analyze the verbal and visual elements found in the Barenbliss advertisement. The method of this research is qualitative. The data were collected through observation and documentation. The data were obtained from Barenbliss’s official website and its official Instagram account. This research used the theory of phrases and the theory of colour meaning to define how different colours are used. The analysis of meaning in this research used the semantic theory. The findings show that the verbal elements primarily occur as noun and adjective phrases. These elements function to provide product information, emphasize product advantages, and attract consumer attention. Most verbal elements convey conceptual and connotative meanings that reflect beauty ideals, product effectiveness, and modern cosmetic trends. Meanwhile, the visual elements are dominated by soft and bright colours such as pink, yellow, and pastel tones. These colours symbolize softness, freshness, and youthfulness, reinforcing the brand image and strengthening the persuasive message. Their integration creates an effective communication strategy that enhances consumer attraction and builds brand identity.